Welfare Effects of the Use of a Combination of Local Anesthesia and NSAID for Disbudding Analgesia in Dairy Calves—Reviewed Across Different Welfare Concerns - Herskin, Mette S.; Nielsen, Bodil H. (Frontiers in Veterinary Science, 2018)
Across the international dairy industry, the vast majority of dairy herds have dehorned cows. Farmers choose to dehorn calves for different reasons such as easier handling of non-horned cattle and reduced risk of injuries in animals and staff. This review focuses on disbudding by use of hot-iron cautery as is practiced by dairy farmers in calves less than 3 months of age. We examine welfare effects of the use of NSAIDs in combination with a local anesthetic including indicators relevant for the three major welfare concerns - affective states, basic health and functioning as well as the possibility to behave naturally. Across indicators of animal welfare, the majority of available evidence suggest that the use of NSAIDs in combination with a local anesthetic is advantageous in terms of animal welfare, and no studies suggest that NSAIDs are a disadvantage to animal welfare. However, irrespective of the welfare concern, use of NSAIDs combined with a local anesthetic does not fully eliminate the welfare challenges from disbudding. Further research is needed in order to fully understand the effects of this medication protocol on calf welfare, including knowledge about the duration of healing and the presence of long-term pain. At present, this lack of knowledge challenges the precise formulation of adequate pain management – in terms of medication protocol, duration, dosage and type of administration.